Housing management practices followed by dairy animal owners in Valsad district of Gujarat - G. P. SABAPARA and L. M. SORATHIYA, P. C. PATEL (Indian Journal of Animal Production and Management, 2020)
A field study was conducted in Valsad district of Gujarat to ascertain the housing management practicesfollowed by dairy animal owners and data were collected from randomly selected 240 dairy animal ownersthrough personal interview with the help of structured interview schedule. The present study revealed thatmajority of respondents provided open type (62.92%) and Pucca type (75%) houses. Majority (83.75%)kept their animals inside the house during day as well as night; 63.75% of animal sheds were near to thedwelling of the respondents and 84.58% of the animal houses were oriented in east-west direction. Majority(90.83%) of respondents had single row system of animal housing and 68.75% had optimum sized animalhouses. About 88.33, 82.5 and 72.92% of the respondents had adequate floor space, light and goodventilation respectively, in their animal sheds. Majority (81.25%) of respondents had clean animal sheds;77.08% had Pucca floors in their animal sheds; 76.7% had slope in floors towards backside of the animalsheds; 83.8% of respondents used cemented type pillars. About 76.7% sheds had single slope type ofroof; 92.1% respondents provided manger to their animals; 30% had Pucca type of manger and 71.7%of animal sheds had provision of Pucca drainage facility for slurry. Only 7.92% of respondents adoptedsome kind of measures to protect the animals from extreme weather conditions and 86.2% respondentsdid not provide bedding material to their animals during winter.